SEA304 - Southeast Asian Art and Heritage March 2002 - PPSKM, Pusat Pengajian Sains Kemasyarakatan (Universiti Sains Malaysia, 2002)
UNIVERSITI SAINS MALAYSIA Second Semester Examination Academic Session 2001/2002 February/March 2002 SEA304 - Southeast Asian Art and Heritage Duration: -2 hours Please check that this examination paper consists of ONE page of printed material before you begin the examination. Answer TWO (2) questions only. Both questions will be given equal marks.